Cognitive impairment and hypertension in older adults living in extreme poverty: A cross-sectional study in Peru - Lazo-Porras M. (2017)
Previous studies have shown that hypertension is a risk factor for cognitive impairment, but whether this association is also present in extremely poor populations in Low Middle Income Countries settings remains to be studied. Understanding other drivers of cognitive impairment in this unique population also merits attention. Methods: We performed a secondary analysis using data from the "Encuesta de Salud y Bienestar del Adulto Mayor", a regional survey conducted in an extremely poor population of people older than 65 years old from 12 Peruvian cities in 2012. The outcome variable was cognitive impairment, determined by a score of ≤7 in the modified Mini-Mental State Examination. The exposure was self-reported hypertension status. Variables such as age, gender, controlled hypertension, education level, occupation, depression and area of living (rural/urban) were included in the adjusted analysis. We used Poisson regression with robust variance to calculate prevalence ratios (PR) and 95% confidence interval (95% CI) adjusting for confounders. Results: Data from 3842 participants was analyzed, 51.8% were older than 70 years, and 45.6% were females. The prevalence of cognitive impairment was 1.7% (95% CI 1.3%-2.1%). There was no significant difference on the prevalence of cognitive impairment between the group of individuals with hypertension in comparison with those without hypertension (PR = 0.64, 95% CI 0.33-1.23). Conclusions: The association described between hypertension and cognitive impairment was not found in a sample of extremely poor Peruvian older adults. © 2017 The Author(s).